PECULIARITIES OF THE LATENT PERIOD OF PRUNUS MONGOLICA MAXIM. AND P. PEDUNCULATA (PALL.) MAXIM. - K. G. Tkachenko (Труды по прикладной ботанике, генетике и селекции)
Relevance. Many species of the genus Prunus s.l. (Rosaceae) are known for their edible fruit, but they are also of interest for  processing into biofuel. Assessment of the quality of reproductive  diasporas (the degree of development of the embryo, endosperm,  and performance) of wild plant species is an indicator of the  prospects for their cultivation. The study of the peculiarities of the latent period gives valuable data for the development of methods for growing potentially useful plant species. The quality of the  emerging fruits and seeds of the wild-growing Prunus mongolica  Maxim. and P. pedunculata (Pall.) Maxim. has not yet been evaluated.Object. Species of the genus Prunus (Rosaceae) collected in the  province of Inner Mongolia (China), which are used for introduction into the Peter the Great Botanical Garden.Materials and methods. Stone fruit of these species were collected  in 2015 and 2016 from wild plants in the province of Inner  Mongolia, China (70 km northeast of the city of Baotou). Methods of germination and fluoroscopic analysis of drupes  were earlier described in detail by K. G. Tkachenko. To measure the  germination, the drupes were divided into two groups: the first was  cleared from the woody endocarp in order to evaluate the laboratory  germination; the second consisted of whole drupes. Both were sown  in October into ceramic pots, and buried for the winter in open  ground to check the field germination. The germinated sprouts were documented in the early June. X-ray analysis of fruits and  seeds was made on a mobile X-ray diagnostic device developed at  St. Petersburg Electrotechnical University (LETI).Results and conclusions. The fruits of the two wild almond species P. mongolica and P. pedunculata harvested in their natural habitats  (70 km to the north-east from the city of Baotou, Inner Mongolia  Province, China) were full-fledged and plump. The main bulk was  attributed to the V and IV classes of development. The laboratory  germination of seeds freed from endocarp was 100% for both  species. Germination of the seeds of the first species was extended  in time (100% sprouted in 60 days), while with the second species,  all seeds sprouted within 15-20 days. The field germination of  unshelled drupes of these species was 57 and 63%, respectively.